The Effects of Regulations on the Florida Ornamental Aquaculture Industry Infographic - Noah C. Boldt; Jonathan van Senten; Carole R. Engle; Eric J. Cassiano; Matthew A. DiMaggio (EDIS)
This infographic accompanies "The Effects of Regulation on Ornamental Aquaculture Farms in Florida" (https://edis.ifas.ufl.edu/publication/FA248), an Ask IFAS factsheet that discusses the results of a study conducted to measure the impact of regulations on ornamental aquaculture farms in Florida using on-farm data from 2018. Florida’s diverse ornamental aquaculture industry has many unique challenges that set it apart from other aquaculture commodity groups. The numerous production techniques, diversity of species, and various market outlets make the ornamental aquaculture industry an intriguing study in how regulations impact the industry. By understanding regulatory impacts, we can streamline efforts to address them.